البعد المعرفي لنظريةالمساءلة لميشال مايير (1950 ) - حمر العين, زهور (جامعة الوادي - university of Eloued, 2021)
منذ انبعاث البحث الحجاجي سنة1958 مع بيرلمان وتيتيكا،عاد الاهتمام من جديد إلى اللغة بصوّرها البلاغية الحاملة لأخلاق الخطيب ومحاولة التّأثير في المتلقي من خلال نص الخطاب وبالتالي الإذعانية والفعل؛ لكن مايير زاد على هذا الأمر كله ببحثه في ابستومولوجيا الحجاج : لما نحاجج؟لما نتكلم؟ إذ لم يكن من أجل الإجابة على سؤال مفترض أسس من خلاله لنظرية المساءلة التي لا تهدف إلى الإقناع و حسب، بل إلى تأسيس المعرفة متجاوزا العقلانية الأوروبية الكلاسيكية الصارمة .نظرية عبرت عن جانب أساس في الفكر البشري وهو المحتمل الذي يبحث دائما من خلال تبادلية سؤال،جواب عن الحقيقة باستثمار اللّغة بألفاظها،تسلسل صيغها وجمالية صورها Abstract: By the emergence of argumentation research in 1958 with Perelman and Tyteca, language has taken back its importance as well as its rhetorical images that bear the morals of the orator and his attempt to influence the recipient through the discourse, hence his response and action. However Meyer added to such issue by researching the epistemology of argumentation: Why do we argue? Why do we speak? Not for the sake of answer a supposed question through which he has established the theory of accountability that does not aim only at persuasion, but rather to establish knowledge, overcoming strict classical European rationality. It is a theory that expresses a fundamental aspect of human thought, which is the potential that always searches the truth through the exchange of question/answer by investing in language and its vocabulary, accordingly the sequence of its structures and images.
مقال
Keywords: ميشال مايير ; ؛ نظرية المساءلة ; الحجاج ; السؤال ; المعرفة; argumentation ; the question ; Knowledge ; Michel Meyer